2012
DOI: 10.1590/s0004-27492012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Pterygium surgery by means of conjunctival autograft: long term follow-up

Abstract: Purpose: To demonstrate the long term of follow-up of the recurrence rate after conjunctival autograft for pterygium surgery. Methods: A total of 112 patients operated for pterygium with conjunctival autografts and with more than one year follow-up were registered. Patients were called for voluntary examinations of their respective ocular surface statuses. Completing the study was only possible in 44 cases. Seven had bilateral pterygium. (N=51 operated pterygium). Results:The mean follow-up time was 49.06 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 37 publications
2
21
2
3
Order By: Relevance
“…However, other studies showed male preponderance eg. Fernandes et al [5] (53.9%), Heurva et al [11] (64%), and Paracha et al [12] (64%).…”
Section: Discussionmentioning
confidence: 94%
“…However, other studies showed male preponderance eg. Fernandes et al [5] (53.9%), Heurva et al [11] (64%), and Paracha et al [12] (64%).…”
Section: Discussionmentioning
confidence: 94%
“…If this holds true, the attendings' recurrence rates may trend higher due to more difficult procedures and higher risk of recurrence. Younger age also increases the risk for recurrence, but age was not significantly different between the experience groups [25,[28][29][30].…”
Section: Discussionmentioning
confidence: 87%
“…Fibrin tissue adhesive has been widely applied in various medical fields, including ophthalmic surgery such as vitreoretinal, glaucoma, ocular surface, cataract and refractive surgery [3,4,5,6,7,8,9,13,14,15,16,17,18]. To our knowledge, this is one of a few reports concerning the applicability of bioadhesive in ocular surface tumor surgery [5,15].…”
Section: Discussionmentioning
confidence: 99%
“…Bioadhesives have the advantage of faster surgical procedure, absence of friction and tension applied to the tissues, uniform adhesion between the handled structures, more comfort, less inflammation and lower risk of tissue necrosis, infections and pyogenic granuloma formation [4,7,13,17,18]. However, its application requires speed and skill of the surgeon, due to the rapid precipitation of its components [4,8,13,18].…”
Section: Discussionmentioning
confidence: 99%